Epidemiological Characteristics of the Corona Virus Disease 2019 in Shaanxi Province Based on "Internet +" Epidemic Monitoring Cloud Platform. Issue 4 (April 2021) - Zhang, Hairui; Feng, Yancheng; Ma, Yonghong; Tan, Jiao; Zhang, Ye; Han, Jiming; Men, Ke
Abstract: Since the outbreak of the Corona Virus Disease 2019(COVID-19), medical staffs have reported cases of hospital infection of COVID-19, which has greatly affected the physical and mental health of medical staff. In order to effectively avoid the immunization situation and prevent the front-line medical staff from collecting information and reporting on the new coronary pneumonia patients, suspected patients, close contacts and other personnel, the possibility of being infected due to various direct and indirect contacts may arise. Information technology, the establishment of a new cloud monitoring platform based on "Internet +" for coronary epidemic outbreaks, and the realization of "zero touch" operation and "paperless" management of the entire process of information collection, confirmation, review and reporting, which greatly reducing the front-line work. The infection risk and labor intensity of personnel have reduced the workload and improved the efficiency of information collection. At the same time, it has also realized automatic statistics, intelligent statistical description and synchronous sharing of the information.